Organizational Readiness for HRIS Integration in Support of Merit-Based System: A Systematic Literature Review - Tia Rifahniari; Reza Fathurrahman (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study examines how organizational readiness for change has been conceptualized in supporting Human Resource Information System (HRIS) integration and merit system implementation within public sector organizations. Despite the growing adoption of HRIS to support transparent and evidence-based personnel management, existing research has largely examined organizational readiness, HRIS integration, and merit systems as separate streams of inquiry. This systematic literature review, covering publications from 2000 to 2025, analyzed twenty-five studies retrieved from Scopus, Web of Science, and Google Scholar using thematic synthesis. The review identified five recurring themes: leadership and management support, change commitment and change efficacy, organizational capacity and digital capability, governance and data integration, and merit-based human resource governance. The findings demonstrate that HRIS integration should be understood as a multidimensional organizational change process rather than a purely technological initiative. Organizational readiness functions as a critical enabling condition influencing whether HRIS integration can be successfully institutionalized and translated into merit-based system implementation. Based on these findings, the study proposes a conceptual framework positioning organizational readiness as the organizational mechanism linking HRIS integration and merit-based systems in the public sector. This article contributes to a more comprehensive understanding of digital transformation and human resource governance by integrating three previously fragmented bodies of literature and provides a foundation for future empirical research in public organizations undergoing administrative and human resource reform.